Perinatal nutrition impacts on the functional development of the visual tract in infants - Normia J.; Niinivirta-Joutsa K.; Isolauri E.; Jääskeläinen S.; Laitinen K. (Nature Publishing Group, 2025)
BACKGROUND AND OBJECTIVE:
We investigated the associations of maternal diet and serum fatty acids during pregnancy and in early infancy on infantile neurodevelopment.
METHODS:
Pattern-reversal visual evoked potentials (pVEP) as depictors of central nervous system maturation were recorded from 56 children when they were 2 years old. Maternal nutrient intakes were calculated from food diaries and fish consumption from questionnaires collected during pregnancy. Serum phospholipid fatty acids were determined by gas chromatography in late pregnancy and from infants at 1 month of age.
RESULTS:
The children of the women who consumed fish three or more times per week during the last trimester of pregnancy had a higher pVEP component P100 amplitude for 60' (mean 23.4, SD 8.1) and 30' (mean 20.4, SD 6.7) of arcminute check sizes compared to those who consumed fish 0-2 times per week (mean 15.0, SD 4.8, p = 0.023, adjusted for birth weight and gender p = 0.058 and mean 13.4, SD 2.0, respectively, p = 0.028, adjusted p = 0.072). Maternal and child serum phospholipid fatty acids correlated with child pVEP measurements.
CONCLUSION:
The results of this small-scale study suggest that fish consumption during pregnancy and perinatal serum fatty acid status may associate with neurodevelopment within visual system during infancy.